2013
DOI: 10.1186/1757-7241-21-53
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a nationwide criteria-based emergency medical dispatch system: A register-based follow-up study

Abstract: BackgroundA criteria-based nationwide Emergency Medical Dispatch (EMD) system was recently implemented in Denmark. We described the system and studied its ability to triage patients according to the severity of their condition by analysing hospital admission and case-fatality risks.MethodsThis was a register-based follow-up study of all 1-1-2 calls in a 6-month period that were triaged according to the Danish Index – the new criteria-based dispatch protocol. Danish Index data were linked with hospital and vita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
150
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 138 publications
(161 citation statements)
references
References 15 publications
7
150
2
2
Order By: Relevance
“…A study from the Central Region of Denmark showed a 51.4% prevalence of high-priority missions. The Danish study also demonstrated a significantly lower annual rate of ambulance missions: 32.2 per 1000 inhabitants compared to 229.5 per 1000 inhabitants in the present study [14]. It is difficult to explain these striking differences between the two countries, but they may be due to differences in the dispatch protocols, EMCC personnel education as well as cultural differences related to contacting the EMCC.…”
Section: Discussioncontrasting
confidence: 57%
“…A study from the Central Region of Denmark showed a 51.4% prevalence of high-priority missions. The Danish study also demonstrated a significantly lower annual rate of ambulance missions: 32.2 per 1000 inhabitants compared to 229.5 per 1000 inhabitants in the present study [14]. It is difficult to explain these striking differences between the two countries, but they may be due to differences in the dispatch protocols, EMCC personnel education as well as cultural differences related to contacting the EMCC.…”
Section: Discussioncontrasting
confidence: 57%
“…The vast majority of patients with hip fracture gain access to acute medical help by dialing the Danish national emergency number (1-1-2) connecting to healthcare professionals in the Emergency Medical Communication Centre (EMCC) who will dispatch an ambulance when needed. Ambulances are dispatched according to a symptom- and criteria-based dispatch protocol which categorizes patients into different levels of urgencies [20]. Alternatively, a GP is contacted and, based on the information obtained from a telephone consultation or a physical examination, the GP can request ambulance transport through the EMCC.…”
Section: Methodsmentioning
confidence: 99%
“…Calls concerning illness and injury are redirected to one of five regional EMCCs, which are staffed with nurses and paramedics as call‐takers, technical staff as dispatchers, and medical doctors as supervisors. The call‐takers use a criteria‐based dispatch protocol, namely the Danish Index for Emergency Care . This protocol divides patients into five emergency levels and into 37 chief complaint groups.…”
Section: Methodsmentioning
confidence: 99%
“…1200/100,000 inhabitants pr. year in the involved regions) . The aim of this study was to investigate whether information about demographic factors and hospitalization history could improve the identification of high‐risk patients in the triage of critically ill and severely injured patients as performed by EMCCs.…”
mentioning
confidence: 99%